Photoinduced flavin-tryptophan electron transfer across vesicle membranes generates magnetic field sensitive radical pairs. (2nd October 2019) - Antill, Lewis M.; Takizawa, Shin-ya; Murata, Shigeru; Woodward, Jonathan R.
ABSTRACT: Due to the photobiology of the flavoproteins DNA photolyase and cryptochrome, electron transfer reactions between flavins and tryptophan are of significant biological relevance. In addition, electron transfer across vesicle membranes has also seen much attention. In this work, we study the electron transfer reaction between flavins and tryptophan across lipid bilayer membranes in 1, 2-dipalmitoyl- sn -glycero-3-phosphocholine small unilamellar vesicles using time-resolved optical absorption microspectroscopy and magnetically affected reaction yield spectroscopy. We demonstrate that riboflavin tetrabutyrate is embedded in the vesicle bilayer and can undergo electron transfer with tryptophan molecules in either the inner water pool or the bulk solution. Remarkably, flavin mononucleotide encapsulated in the inner water pool can undergo electron transfer across the vesicle bilayer to generate a magnetically sensitive radical pair with tryptophan molecules located in the bulk solution. The observed kinetics suggest that back electron transfer occurs between radical pairs generated by diffusive reencounter, either in the vesicle surface water or via electron hopping through degenerate electron exchange. GRAPHICAL ABSTRACT: